Pengaruh Kesulitan Belajar Dan Gaya Belajar Terhadap Prestasi IPSPada Siswa Kelas Atas SD Muhammadiyah 4 KandangsapiTahun Ajaran 2015/2016 - ASTARI, DESY, Drs. Mulyadi S. K., SH.,M.Pd (2016)
Effect of Learning Disabilities and Learning Styles Of Achievement IPS Students in Upper Class SD Muhammadiyah 4 Kandangsapi Academic Year 2015/2016 By: Desy Astari, A510120035, Department of Primary School Teacher Education, the Faculty of Education, University of Muhammadiyah Surakarta, 2016 This study aims to determine: (1) the effect on the achievement of learning difficulties in class IPS on SD Muhammadiyah 4 Kandangsapi the Academic Year 2015/2016, (2) the influence of learning styles on student achievement IPS in an upscale SD Muhammadiyah 4 Kandangsapi the Academic Year 2015 / 2016, (3) the effect of learning difficulties and learning styles on student achievement IPS in an upscale SD Muhammadiyah 4 Kandangsapi Academic Year 2015/2016. This type of research is quantitative research. Subjects in this study are students of upper class (4,5, and 6) 4 Kandangsapi SD Muhammadiyah Surakarta in 2015/2016. Data collection techniques used are questionnaires and documentation. Mechanical testing instruments used are validity and reliability testing. Techniques used prerequisite test is the test of normality and linearity test. Data analysis technique used is multiple regression analysis, t-test, f, coefficient of determination and looking for the contribution given. The first hypothesis of the calculation results obtained by the regression coefficient is negative (b1 = -0.145) and value -thitung> -ttabel (-2.105> 2.024) and sig. <0.05 (0.042 <0.05). From the calculation of the second hypothesis obtained positive regression coefficient (b2 = 0.221) and tcount> t table (2.175> 2.024) and sig. <0.05 (0.036 <0.05). The third hypothesis of the calculation results obtained Fhitung> F table (14.080> 3.23) and a significance value <0.05 (0.000 <0.05). So that the conclusions of this study are (1) the difficulty of learning effect on student achievement IPS in an upscale SD Muhammadiyah 4 Kandangsapi the Academic Year 2015/2016, (2) learning styles affect the achievement of IPS grade students on SD Muhammadiyah 4 Kandangsapi the Academic Year 2015/2016 , (3)the difficulty of learning and learning styles affect the achievement of IPS grade students on SD Muhammadiyah 4 Kandangsapi Academic Year 2015/2016. Keywords: learningdisabilities, learningstyles, and learningachievement